Assessment of Spatial Differentiation of Financial Independence of Poviats in Poland (2007–2019) - Paweł Dziekański; Magdalena Wrońska; Mansoor Maitah; Oleksandr Novoseletskyi (Transylvanian Review of Administrative Sciences, 2022)
A poviat is an independent entity with autonomy in the use of resources in the process of carrying out public tasks. Its local economic, financial and social resources, as well as information resources, determine the level of development. The basis for the proper and effective operation of poviats is the provision of appropriate financial resources. They consist of both the so-called own income as well as transfers from the state budget in the form of, inter alia, general subsidies and targeted subsidies. The main aim of the article is to assess the spatial differentiation of the level of financial independence of poviats in Poland in 2007-2019 using a synthetic measure. The empirical data on poviats in Poland was collected through information available from the Local Data Bank of the Central Statistical Office. The financial independence of poviats is radically diversified. There are significant differences regarding its level between the east and west of Poland. The western part of the country is characterized by better independence and financial situation. The study showed that the level of financial independence was shaped primarily by own income, income from PIT (personal income tax) and CIT (corporate tax), transfers from the state budget, and investment expenditure. The development of poviats depends on financial independence. The possessed financial resources are the basis for the operation and the condition for the implementation of its current and investment tasks. The potential of the poviat is built, among others, by professional activity of inhabitants, local labor market, entrepreneurship, infrastructure, condition of the natural environment, financial situation, increase in the quality and scope of public services and investments. Financial independence is correlated with the level of local development. It translates into disproportions in terms of the possibilities of meeting local needs, meeting current and future obligations.